2022
DOI: 10.1021/acs.jnatprod.2c00147
|View full text |Cite
|
Sign up to set email alerts
|

Modified ent-Abietane Diterpenoids from the Leaves of Suregada zanzibariensis

Abstract: The leaf extract of Suregada zanzibariensis gave two new modified ent -abietane diterpenoids, zanzibariolides A ( 1 ) and B ( 2 ), and two known triterpenoids, simiarenol ( 3 ) and β-amyrin ( 4 ). The structures of the isolated compounds were elucidated based on NMR and MS data analysis. Single-crystal X-ray diffraction was used to establish the absolute configurations of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Kalenga reported that modified ent-abietane diterpenoids with a terminal olefinic bond at C-4, such as in compounds 58 and 59, are rare. The terminal double bond at C-4 is proposed to arise through an enzymatic 1,2-methyl shift, either of CH 3 -18 or CH 3 -19, from C-4 to C-3, followed by dehydrogenation [46]. The suggested biosynthesis for compounds 58 and 59 is shown in Scheme 2 [46].…”
Section: Intermediate See May Undergo Cyclization To Yield (D) Dehydr...mentioning
confidence: 99%
See 4 more Smart Citations
“…Kalenga reported that modified ent-abietane diterpenoids with a terminal olefinic bond at C-4, such as in compounds 58 and 59, are rare. The terminal double bond at C-4 is proposed to arise through an enzymatic 1,2-methyl shift, either of CH 3 -18 or CH 3 -19, from C-4 to C-3, followed by dehydrogenation [46]. The suggested biosynthesis for compounds 58 and 59 is shown in Scheme 2 [46].…”
Section: Intermediate See May Undergo Cyclization To Yield (D) Dehydr...mentioning
confidence: 99%
“…The terminal double bond at C-4 is proposed to arise through an enzymatic 1,2-methyl shift, either of CH 3 -18 or CH 3 -19, from C-4 to C-3, followed by dehydrogenation [46]. The suggested biosynthesis for compounds 58 and 59 is shown in Scheme 2 [46]. The oxidation of ent-copalyl PP leads to the production of ent-pimaradiene.…”
Section: Intermediate See May Undergo Cyclization To Yield (D) Dehydr...mentioning
confidence: 99%
See 3 more Smart Citations